A case of delayed‐onset scarring alopecia in a 75‐year‐old woman. (1st August 2020) - Maguire, M.; Drumm, C.; Woods, G.; Mullally, W.; Redmond, M.; Grogan, L.; O'Kane, M.
Abstract: Click here for the corresponding questions to this CME article.